PREPARATION AND PHYSICOCHEMICAL ANALYSIS OF POLYMER COMPOSITES FROM RECYCLED PET WASTE - Norbutayev, S. Q.; Tavashov, Sh. Kh. (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: This study investigates the physicochemical properties of polymer composite materials based on recycled PET and CaCO3. Method: The thickness of the samples was selected in compliance with the standard requirements: 3,49 mm for sample 1, 3,43 mm for sample 2, and 3,91 mm for sample 3.The experiment was initiated at an ambient temperature of 22,5°C, with a controlled heating rate of 50°C per hour. Under an applied load of 10 N, the penetration of the needle to a depth of 1 mm for the first sample was achieved after 118,68 minutes, corresponding to a temperature of 152,4°C. Results: The results indicate that optimal performance is achieved at 5–15% CaCO3, demonstrating the potential of recycled PET composites for cost-effective industrial applications. Novelty: The results indicate that optimal performance is achieved at 5–15% CaCO3, demonstrating the potential of recycled PET composites for cost-effective industrial applications.